Anatomy Education and Training Methods in Oral Surgery and Dental Implantology: A Narrative Review - Carlo Barausse; Pietro Felice; Roberto Pistilli; Gerardo Pellegrino; Lorenzo Bonifazi; Subhi Tayeb; Irene Neri; Foteini-Dionysia Koufi; Antonietta Fazio; Maria Vittoria Marvi; Lucia Manzoli; Stefano Ratti (Dentistry Journal)
Background: Oral and implant surgery represent highly specialized fields within dentistry that require a deep understanding of complex anatomical structures, together with practical hands-on experience. The present review examines common trends in oral and implant surgery training, focusing on how traditional methods like donated body dissection coexist with different and modern educational tools, and highlights the pros and cons of the different approaches in order to optimize training outcomes. Methods: A systematic literature search was carried out using the databases PubMed and Cochrane Library including the last 10 years of published articles about training in oral surgery and implantology. Starting from a total of 1319 studies, 47 were included to be carefully evaluated, and 20 studies were finally selected for this narrative review. The studies utilize methodologies such as randomized controlled trials (RCTs), cross-sectional surveys, case–control studies, and systematic reviews. The results were thematically organized, highlighting key quantitative outcomes and drawing connections between the different educational approaches. Results: From the narrative review, it emerged that oral and implant surgery training requires a careful balance between traditional methods, such as donated human body dissection, and modern technological advancements like virtual simulations and synthetic models. While animal and synthetic models have specific uses, their application remains limited in replicating the full complexity of human anatomy. These last technologies offer flexibility and expanded access to education but do not substitute for the hands-on experience gained through donated human body dissection. Conclusions: As educational institutions continue to evolve their training programs, ensuring access to human body dissection remains of paramount importance. Combining the strengths of both traditional and modern approaches may help optimize oral and implant surgery education, enhancing student preparedness without overlooking the critical value of direct anatomical experience.